PENINGKATAN KUALITAS ABON NANGKA MUDA DENGAN SUBSTITUSI TEPUNG TEMPE. KAJIAN DARI KANDUNGAN PROTEIN DAN TINGKAT KESUKAAN KONSUMEN - Rosida, Dwi Agustiyah; Widodo, Richardus (Heuristic, 2015)
In recent days, a modern society especially those who live in town, trend to consumption more nutritious food with low in calorie and cholesterol free. Synthetic â€œabonâ€ made from young jackfruit is one of good vegetable food which are have potentially prized to develop. The lack of protein, can be handled by protein fortification. Tempe is one of Indonesian traditional food with rich in protein can be considered as fortification agent. Research on tempe flour as fortification agent of young jackfruit â€œabonâ€ has been done. The purpose of the research is to know how many tempe flour can be added to got optimum acceptability of the product. The experiment carried out in 3x2 factorial randomized block design. The first factor are 2,5 %, 5 %, and 7,5 % w/w of tempe flour, and the second factors are treatment of tempe before floured, that is steamed and not steamed. Variance analysis of protein content shows that 1) there is significant difference among the 3 level of first factor (P<0.01), either of the 2 level of the second factor (P<0.01). Combination of 7,5 % w/w and not steamed tempe flour give the best result with 9,886 % in protein content. 2) there is not significant interaction effect between the two factors analyzed against the protein content (P>0.05). 3) Sensory test of texture and flavor show no difference score among the treatments (P>0.05) while for the color of the product, the panelist give different score (P<0,01)Kata Kunci : abon nangka muda, fortifikasi, tepung tempe